2D modeling and simulation of deformation bands' effect on fluid flow: Implications for hydraulic properties in siliciclastic reservoirs. (May 2022) - Souza, Franklyn Macedo de; Gomes, Igor Fernandes; Nogueira, Francisco Cézar Costa; Vasconcelos, David Lino; Canabarro, Bruno; Souza, Jorge André Braz de; Guimarães, Leonardo José do Nascimento; Beserra, Leila Brunet de Sá
Abstract: Deformation bands can influence fluid flow within reservoirs, mainly acting as flow barriers. This study aims to characterize deformation bands and evaluate the influence of these structures on fluid flow through 2D modeling and numerical simulation using the equivalent permeability tensor computed numerically through a flow-based upscaling procedure in siliciclastic reservoirs. To do so, we analyze arkosic sandstones of the Antenor Navarro Formation in the Rio do Peixe Basin, NE Brazil. The characterization of deformation bands involved: 1) acquisition of aerial imagery using a drone; 2) conducting direct field-based structural analysis along one scanline (frequency of deformation bands/m); and 3) collection of samples in the field to perform petrophysical (porosity and permeability) tests. After the characterization phase, we built a 2D geological model using the previously acquired parameters and performed a single-phase numerical flow simulation of water using finite element code. We simulated four different horizontal and vertical flow scenarios for both measured and exaggerated host rock permeability. Our structural analysis demonstrated that the deformation bands preferentially strike NE–SW, with secondary E–W– to N–S–orientations. Our petrophysical analysis showed that samples affected by deformation bands have lower porosity (by up to two orders of magnitude) and permeability (by up to four orders of magnitude) values than samples collected in the host rocks. The numerical fluid flow simulation allowed us to conclude that the deformation bands act as partial flow barriers where the hydraulic head can indicate the barrier effect intensity. Pressure drops between host rock regions separated by deformation bands reached values from 10 to 40%, depending on the fluid flow direction, especially for cases with a high contrast between the permeability values (three orders of magnitude) of the deformation bands and the host rock. The results of this study focus on the importance of contrasts in permeability measurements between deformation bands and host rocks, which could help to enhance understanding of the behavior of the deformation bands as partial fluid flow barriers, as well as their implications for hydraulic properties in deformed siliciclastic reservoirs. Highlights: 2D numerical modelling and simulation flow in a deformation bands fault zone. Permeability contrast between deformation bands and host rock. Fluid flow behavior is influenced by their orientation regarding the band geometry. Discontinuities in the pressure field highlight the band influence on the fluid flow.